Seismic behavior of novel GFRP bar reinforced concrete beam-column joints internally reinforced with an FRP tube. (15th December 2022) - Lin, Guan; Zeng, Jun-Jie; Liang, Sheng-Da; Liao, JinJing; Zhuge, Yan
Highlights: A type of novel FRP-RC beam-column joints with an internal FRP tube is proposed to enhance the energy dissipation capacity. The FRP tube implemented in the joint could shift the failure mode of the joints under seismic loadings. The thickness of the internal FRP tube has little influence on the hysteretic behavior of the joints. The effect of fiber orientation of the FRP tube on the seismic behavior of the joints is evident. Abstract: Due to many advantages, fiber-reinforced polymer (FRP) bars have been considered as a promising alternative to steel bars in reinforced concrete (RC) structures. The use of FRP bars in beam-column joints has been reported in the literature. However, it has been found that the energy dissipation capacity of an FRP-RC beam-column joint is dramatically lower than that of the corresponding steel-RC joint. The present study attempts to develop a novel form of FRP-RC beam-column joints with superior energy dissipation capacity. The proposed joints incorporate an internal FRP tube in the joint zone, which provides confinement to the inner concrete and shear resistance of the joint. Compared with existing reinforcement techniques using stiffeners or internal diaphragms, the proposed use of an internal FRP tube is much easier to be implemented. To demonstrate the advantages of the proposed FRP-RC beam-column joints, an experimental program consisting of 6 FRP-RC beam-column joint specimens was carried out. The effects of fiber type, thickness, and fiber orientation of the FRP tube in the joint zone were investigated. The test results in terms of failure modes, hysteretic behaviors, and energy dissipation capacities of the test specimens were discussed in detail. The test results demonstrated the efficiency of the FRP tube, especially the one with a fiber angle of ±45°, in enhancing the energy dissipation capacity of FRP-RC beam-column joints.